Sensing the Pulse of Urban Refueling Behavior - Zhang, Fuzheng; Wilkie, David; Zheng, Yu; Xie, Xing (Proceedings of the 15th ACM International Conference on Ubiquitous Computing, 2013)
Urban transportation is increasingly studied due to its com-plexity and economic importance. It is also a major com-ponent of urban energy use and pollution. The importance of this topic will only increase as urbanization continues around the world. A less researched aspect of transporta-tion is the refueling behavior of drivers. In this paper, we propose a step toward real-time sensing of refueling behav-ior and citywide petrol consumption. We use reported tra-jectories from a fleet of GPS-equipped taxicabs to detect gas station visits, measure the time spent, and estimate overall demand. For times and stations with sparse data, we use collaborative filtering to estimate conditions. Our sys-tem provides real-time estimates of gas stations’ waiting times, from which recommendations could be made, an indicator of overall gas usage, from which macro-scale economic decisions could be made, and a geographic view of the efficiency of gas station placement.